Dampak Bantuan Langsung Tunai (BLT) Dana Desa Covid-19 Terhadap Perekonomian Masyarakat - Yendra, Musfi; Malfa Wetsi, Windi Putri (Jurnal Ilmiah Ekotrans & Erudisi, 2021)
The Village Fund Direct Cash Support (BLT) is a form of financial aid provided to impoverished households in rural areas. This support is derived from the Village Fund and aims to alleviate the adverse effects of the Covid-19 epidemic. The Village Fund BLT provides a monthly amount of Rp. 600,000 to eligible impoverished families for three months, followed by Rp. 300,000 per month for the subsequent three months. This study aims to determine the economic status of the residents of Nagari Sungai Tunu during the onset of the COVID-19 pandemic. What challenges arise with implementing the distribution of Village Fund BLT, and what measures are used to address these issues? To assess the economic effects of the COVID-19 Village Fund BLT on the Nagari Sungai Tunu community. The research employed a descriptive methodology with a qualitative approach. The data sources utilized in this research comprise primary data acquired through direct observations, interviews with 11 informants, and secondary data gained from papers and reports. The research findings indicate that the initial phase of the Village Fund BLT, implemented in 2020, significantly influenced the economy of the residents of Nagari Sungai Tunu. One hundred sixty-nine families received the Covid-19 Village Fund BLT, IDR 600,000 over three months. The extended duration spans from May to July. The COVID-19 Village Fund BLT aims to address the living requirements of the residents of Nagari Sungai Tunu amidst the pandemic. The community utilizes financial assistance to procure essential commodities and fulfill the educational needs of children.